Chemical Profile and Hematoprotective Activity of Artisanal Jabuticaba (Plinia jabuticaba) Wine and Derived Extracts - Raissa Lima; Marcos Vinicius T. Silva; Brendo A. Gomes; Ellis Helena B. C. Macedo; Michele N. Santana; Ana Claudia F. Amaral; Jefferson R. A. Silva; Pollyane G. Corrêa; Ronoel Luiz O. Godoy; Manuela Cristina P. A. Santiago; Suzana G. Leitão; Rosineide C. Simas; et al. (Fermentation, 2023)
The alcoholic fermentation of jabuticaba berries (Plinia spp.) originates from a beverage with an intense taste and aroma, popularly known as jabuticaba wine (JW). In addition, polyphenols transferred from fruit peels to the final product turn this beverage into a promising source of bioactive agents. Here, the chemical profile and antioxidant potential of artisanal JW and derivative extracts were determined. Volatile organic compounds were determined by HS-SPME/GC-MS analysis. The wine was dried by lyophilization and subjected to liquid-liquid partitioning (water: ethyl acetate), resulting in three fractions (JWF1-3). ABTS•+ and DPPH•+ scavenging assays were performed to evaluate the antioxidant capacity. In addition, the extracts’ hematoprotective activity was evaluated against oxidative stress. Finally, the extracts were analyzed by LC-HRMS/MS. HS-SPME/GC-MS analysis highlighted 1,8-cineole as the main compound that contributes to the camphor/mint flavor. JWF2 and JWF3 displayed the highest antioxidant capacity. JWF2 stood out for preventing oxidative damage in red blood cells at 7.8 µg·mL−1 The maximal protection of ascorbic acid occurred at 8.8 µg·mL−1. The LC-HRMS/MS analysis allowed the annotation of seventeen compounds, most of them with recognized antioxidant activity such as anthocyanins, catechins, flavanols, and phenolic acids. The results presented herein reinforce JW as a pleasant beverage with bioactive potential.